Association between physical activity, participation in Physical Education classes, and social isolation in adolescents - Simone José dos Santos; Carla Menêses Hardman; Simone Storino Honda Barros; Carolina da Franca Bandeira Ferreira Santos; Mauro Virgilio Gomes de Barros (Elsevier, 2015)
Objective: To analyze the association between physical activity, participation in Physical Education classes, and indicators of social isolation among adolescents. Methods: This was an epidemiological study based on secondary analysis of data from a representative sample of students (14-19 years) from public high schools (n = 4,207). Data were collected through the questionnaire Global School-based Student Health Survey. The independent variables were the level of physical activity and enrollment in Physical Education classes, while the dependent variables were two indicators of social isolation (feeling of loneliness and having few friends). Descriptive and inferential procedures were used in the statistical analysis. Results: Most of the adolescents were classified as insufficiently active (65.1%) and reported not attending Physical Education classes (64.9%). Approximately two in each ten participants reported feeling of loneliness (15.8%) and, in addition, about one in each five adolescents reported have only one friend (19.5%). In the bivariate analysis, a significantly lower proportion of individuals reporting social isolation was observed among adolescents who referred higher enrollment in Physical Education classes. After adjustment for confounding variables, binary logistic regression showed that attending Physical Education classes was identified as a protective factor in relation to the indicator of social isolation 'having few friends,' but only for girls. Conclusions: It was concluded that participation in Physical Education classes is associated with reduced social isolation among female adolescents. Resumo: Objetivo: analisar a associação entre a prática de atividades físicas, a participação nas aulas de Educação Física e indicadores de isolamento social em adolescentes. Métodos: Trata-se de um estudo epidemiológico transversal, baseado na análise secundária de dados, a partir de uma amostra representativa de estudantes (14-19 anos) do ensino médio da rede pública estadual (n = 4.207). Os dados foram coletados através do questionário Global School-based Student Health Survey. As variáveis independentes foram o nível de atividade física e a participação nas aulas de Educação Física, enquanto as variáveis dependentes foram dois indicadores de isolamento social (sentimento de solidão e ter poucos amigos). Na análise estatística, recorreu-se a procedimentos descritivos e inferenciais. Resultados: A maioria dos sujeitos foi classificada como insuficientemente ativa (65,1%) e relatou não participar das aulas de Educação Física (64,9%). Aproximadamente dois em cada dez participantes (15,8%) referiram sentimento de solidão e cerca de um em cada cinco (19,5%) reportaram ter até um amigo. Na análise bivariada, verificou-se uma proporção significativamente inferior de isolamento social entre os adolescentes que participavam das aulas de Educação Física. Na regressão logística binária, após ajustamento de variáveis, verificou-se que a participação nas aulas de Educação Física foi identificada como fator de proteção em relação ao indicador de isolamento social "ter poucos amigos", mas somente entre as moças. Conclusões: Concluiu-se que a participação nas aulas de Educação Física está associada à menor isolamento social em adolescentes do sexo feminino. Keywords: Social isolation, Friends, Physical activity, Physical Education, Adolescent, Palavras-chave: Isolamento social, Amigos, Atividade física, Educação física, Adolescente